Surgery of the major salivary glands and its impact on salivary flow—A review. (26th November 2018) - Burghartz, Marc; Hackenberg, Stephan; Sittel, Christian; Hagen, Rudolf
Abstract : Objective: The aim of this study was to bring attention to a rather unnoted side effect of salivary gland surgery–reduced salivary flow. Methods: A systematic PubMed, Cochrane Library, LIVIVO, and Embase databases search was performed to identify relevant articles. Results: Eight studies matched the inclusion criteria. All studies described an association between salivary gland surgery and reduced salivary flow. In five of the eight studies, patients reported on xerostomia after salivary gland surgery. Conclusions: Head and neck surgeons should inform their patients more accurately about reduced salivary flow and possible xerostomia after salivary gland surgery, and focus more on conservative strategies and minimally invasive techniques. Laryngoscope, 129:2053–2058, 2019